Depression Level Difference Between Gifted and Non-gifted Medical Students - Firas Farisi Alkaff; Adila Taufik Syamlan; Michael Jonatan; Ricardo Adrian Nugraha; Tan Nicko Octora; Azimatul Karimah (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2018)
Introduction: Depression is a common mental health conditions in the world. Compare to general population, the prevalence of depression in medical students are higher. There are several risk factors that might contribute to the higher rate of depression in medical students, including being a gifted student. However, no study has been published regarding the depression of the gifted medical students until now.Aim: To find out the difference in the level of depression between gifted and non-gifted medical students. Methods: This study was a descriptive cross-sectional study, conducted from October to December 2016. Subjects were third year medical students from Faculty of Medicine Universitas Airlangga. There were 2 groups in this study. Samples from gifted students group was obtained using total sampling method, while number of samples from non-gifted students group was equated with gifted students group. Depression was measured using Beck Depression Inventory (BDI). Mann-Whitney U test was used for statistical analysis. Results: 34 students, 17 students in the gifted students group and 17 students in the non-gifted students group, were included in this study. Based on the BDI score results category, 2 students from the gifted students group and 1 student from non-gifted students group were in the mild category, and 1 student from the gifted students group was in the borderline category. The highest BDI score in gifted students group were 14, while in non- gifted students group were 17. There was no significant difference of the BDI score and BDI category between groups (p = 0.154; 0.951, respectively).Conclusion: There was no significant difference of depression level between gifted and non-gifted medical students.